PENGARUH VARIASI RASIO TRANSMISI TERHADAP KONSUMSI ENERGI SEPEDA MOTOR LISTRIK KONVERSI PADA KONDISI JALAN MENDATAR - Wartama, I Ketut Agus Milan; Widiyarta, I Made; Darma, I Wayan Arya (Teknik Desain Mekanika, 2024)
Abstract Currently, many people use motorized vehicles for daily activities. This increases fuel consumption and depletes oil reserves, while also causing pollution that affects air quality and the environment. Electric motor conversion is the best alternative to replace gasoline engines from economic, environmental, and social aspects. In this study, a 2006 Mio Sporty motorcycle was converted into an electric motorcycle using a battery as an energy source, replacing gasoline. This conversion changes the motor components, with some components removed and new components added. The transmission ratio was varied into three: adding 12 rings, 2 rings, and no ring addition, and tested on a 5 km road with and without a passenger load at speed control I and II. The test results showed that the transmission without ring addition (ratio 0.81) achieved the highest speed. Repeated testing three times showed that the transmission ratio of 0.92 without passenger load consumed energy at 0.029 kWh/km, with an average travel time of 13.02 minutes for a 5 km distance. Keywords: Transmission Ratio, Testing of Converted Electric Motorcycles, Energy Consumtion